PENGEMBANGAN BAHAN AJAR MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS V SEKOLAH DASAR - Eni Marta; Hasrijal Hasrijal (JURNAL PENDIDIKAN ROKANIA, 2018)
The purpose of teaching and learning with the aim of improving the effectiveness and efficiency of learning objectives. This research was conducted at SDN 001 Rambah and at SDN 008 Rambah. Type of research is research development (research and development). The development model used is a 4-D model consisting of define, design, development and dessiminate. The define stage is done curriculum analysis, material analysis, and student analysis. Design stage is designed on learning tools in the form of RPP and teaching materials. Development phase is validity test through device validation sheet, practicality test through observation sheet of RPP implementation, teacher and student response questionnaire, effectiveness test obtained from student activity assessment. The dessiminate stage is carried out with limited scaling of devices. The results of the research on the define stage obtained curriculum analysis, and studentanalysis. The results of the research at the design stage obtained RPP and teaching materials that are designed following the learning steps using the PBL model. The results of research on the development stage of the validity test obtained the data that the average percentage of RPP is 89% and the percentage of teaching materials of the instrument validation is 90.8%. Practical test results from the implementation of RPP percentage is 92.04%, teacherresponse questionnaire is 91.02% and student response questionnaire is 89.2%. Furthermore the effectiveness test results obtained from student activity with percentage 88.4%.